THE INFLUENCE OF WORK CHARACTERISTICS, ORGANIZATIONAL CULTURE, AND LEADERSHIP ETHICS ON THE LOYALTY OF EMPLOYEES IN INDO FURNITURE - Budi Alamsyah Siregar; Dewi Suma; R. Djoko Goenawan (PENANOMICS: International Journal of Economics, 2022)
Every company considers human resources the most important asset in developing a business or company itself. This study aims to determine whether the characteristics of the work affect the Loyalty of Indo Furniture Employees. To find out whether Organizational Culture affects Indo Furniture's Employee Loyalty. To find out whether Leadership Ethics affect the Loyalty of Indo Furniture Employees. To determine whether work characteristics, organizational culture, and leadership ethics affect employee loyalty. The research approach used by the author is to use a quantitative approach. Results: the effect of job characteristics obtained t value 16.992 with a value of t sig = 0, 000 < 0.05). Thus, it can be stated that the Job Characteristics partially affect Indo Furniture Employees' Loyalty. The influence of organizational culture obtained t value of 2.436 with a value of sig = 0.001 > 0.05). Organizational Culture Affects Indo Furniture's Employee Loyalty. The influence of Leadership Ethics obtained t-value of 3.612 with a value of sig = 0.001 > 0.05. Leadership Ethics Affects Indo Furniture's Employee Loyalty.